Addressing the Needs of Adolescents With Autism Spectrum Disorder: Considerations and Complexities for High School Interventions. (April 2015) - Kucharczyk, Suzanne; Reutebuch, Colleen K.; Carter, Erik W.; Hedges, Susan; El Zein, Farah; Fan, Hannah; Gustafson, Jenny R.
The outcomes of students with autism spectrum disorder (ASD) are driving the field to address how secondary education might be optimally designed and delivered. We conducted 28 focus groups across four states to explore the contexts, considerations, and complexities associated with delivering and combining evidence-based interventions to meet the needs of adolescents with ASD from the vantage point of 152 practitioners, parents, and other key stakeholders. Participants emphasized the inadequacy of prevailing intervention approaches in secondary schools, underscored the importance of attending to feasibility and alignment with the diverse needs of students with ASD, and stressed the need for broader awareness and training efforts surrounding autism. We offer recommendations for designing comprehensive interventions and incorporating stakeholder feedback into such undertakings.